(untitled) (diségno, 2024)
We open our reflection with an examination of the words or phrases that are the key of this third topic: ‘representation’, ‘landscape’, ‘imaginary drawings’ and ‘utopian visions’. It seems rather superfluous to dwell on the first one, ‘representation’, since we architects and teachers of the disciplines of representation have already written and spoken so much about it. We know that it is a term of medieval origin that indicates the ‘image’ or the ‘idea’ or both. [read more]